Evaluation and selection of yeasts as potential aroma enhancers for the production of dry-cured ham - Xiaohui Gong; Ruifang Mi; Xi Chen; Qiujin Zhu; Suyue Xiong; Biao Qi; Shouwei Wang (Food Science and Human Wellness)
Yeasts play a critical role in the flavor formation of dry-cured ham. In this study, 41 yeast isolates from the dry-cured ham at different processing stages were evaluated for their technological properties. Debaryomyces hansenii was the most dominant yeast and has been detected at each phase of dry-cured ham, followed by Candida zeylanoides which was mainly detected in salting phase. Yarrowia bubula and Yarrowia alimentaria were found at the first two-phase of dry-cured ham. All isolates of yeast showed enzymatic activities against milk protein and tributyrin, while only 4 strains displayed proteolytic activity on meat protein. Yeast strains were grown in a meat model medium and volatile compounds were identified. The result showed that inoculated yeast strains could promote the production of volatiles and there were significant differences among strains. D. hansenii S25 showed the highest production of volatile compounds, followed by the strain C. zeylanoides C4. D. hansenii S25 was the highest producer of alcohols showing the highest production of benzeneethanol and 3-(methylthio)-1-propanol. Based on OAV and PLS analysis, D. hansenii S25 was strongly correlated with overall flavor and key volatile compounds of dry-cured ham, which could be selected as potential starter cultures.